Тheoretical Aspects of Studying of Сollocations - Сhorikulovnа, Mеhmonovа Уulduz (International Journal on Integrated Education, 2023)
This article is devoted to the theoretical aspects of studying of collocations.by ranslation of texts with lexicogrammatical resources of functional equivalence in English and Uzbek languages. The expression of translation of texts with lexicogrammatical resources have been analyzed and differences identified.